2021
DOI: 10.11113/ijbes.v9.n1.890
|View full text |Cite
|
Sign up to set email alerts
|

How to Reveal the Meaning of Space in Vernacular Architecture?

Abstract: Vernacular architecture is a modest style of building used to maintain the balance of human relations with nature. This architectural style is specific to a region and passed down from one generation to another to embody cultural values. However, its development is currently facing globalization and modernization challenges, thereby leading to a gradual shift of this ancestral heritage to modern buildings. Change is unavoidable due to continuous evolution, however, the meaning inherent architecture buildings n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…(Icomos, 1999, pp. 1-2) Por su parte, Oliver (1978), Maldonado Flores (2009 y Manurung et al (2021) indican que se trata de una arquitectura didáctica, ya que implica un proceso constructivo donde es posible advertir sucesivas transformaciones y adaptaciones, de acuerdo a la composición familiar, a las actividades productivas y según el trasfondo cultural dominante.…”
Section: Aproximaciones Al Concepto De Patrimonio Ruralunclassified
“…(Icomos, 1999, pp. 1-2) Por su parte, Oliver (1978), Maldonado Flores (2009 y Manurung et al (2021) indican que se trata de una arquitectura didáctica, ya que implica un proceso constructivo donde es posible advertir sucesivas transformaciones y adaptaciones, de acuerdo a la composición familiar, a las actividades productivas y según el trasfondo cultural dominante.…”
Section: Aproximaciones Al Concepto De Patrimonio Ruralunclassified
“…Setiadi [37] stated that local wisdom is part of a dynamic cultural tradition, and it can adapt to new unique creations. The local wisdom was also explained as a distinctive form of community expression and can adapt to the times without losing its local character [18,30,32,36]. This means the positive values inherent in the culture need to be preserved as essential lessons for future generations [19,20,38] (see Table 1).…”
Section: Culture and Local Wisdommentioning
confidence: 99%
“…It is important to note that vernacular building space is a place for social activities and contains historical meaning that can be applied to modern buildings. Moreover, its functionality responds to changes and the needs of different times while maintaining the local essence [18]. Ceylan [19] showed that the unique character of the architecture needs to be protected and maintained to allow future generations to also benefit from design features.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation is defined as changing a form or expression into a new type of form with the same meaning from the function, characteristic, location, appearance, state, and nature [8]. Various attempts are being made to restore the loss of local wisdom, culture, and social values caused by traditional architectural transformations [9].…”
Section: Introductionmentioning
confidence: 99%